THE USE OF “POLISI NUMPANG TANYA” GAME TO TEACH SPEAKING OF THINGS AROUND ME TO THE SEVENTH GRADERS (RETAIN, 2015)
Abstract Teaching speaking is one of skills which should be taught in the school. In teaching speaking there should be fun way to make students enjoy while learning. So the teachers have to use the right technique or media to teach adolescent learners especially seventh graders. Based on the reality, the researcher used “polisi numpang tanya” game as a technique to teach speaking of thing around me. This study presents the use of “polisi numpang tanya” game. Beside that, the researcher also describes the students’ responses on using the technique. To get the data needed, the researcher uses observation checklist, interview, and questionnaire as the instruments. The observation was conducted twice. The data collected were analysed qualitatively through the process of describing, sorting and analysing. The result showed that the “polisi numpang tanya” was easily implemented. The responses of the students showed that they were very excited to speak through the game. It means that the technique could be used in teaching speaking to the seventh graders. Keywords: “Polisi numpang tanya”, Speaking, Seventh graders. Abstrak Pengajaran berbicara merupakan salah satu keterampilan yang harus diajarkan di sekolah. Dalam mengajar berbicara harus ada cara yang menyenangkan untuk membuat siswa dapat menikmati pelajaran dengan senang. Jadi, guru harus menggunakan teknik atau media yang tepat untuk mengajar peserta didik remaja terutama kelas tujuh. Berdasarkan kenyataan tersebut, peneliti menggunakan permainan